Femoral head necrosis: A finite element analysis of common and novel surgical techniques. (October 2017) - Cilla, Myriam; Checa, Sara; Preininger, Bernd; Winkler, Tobias; Perka, Carsten; Duda, Georg N.; Pumberger, Matthias
Abstract: Background: Femoral head necrosis is a common cause of secondary osteoarthritis. At the early stages, treatment strategies are normally based on core decompression techniques, where the number, location and diameter of the drilling holes varies depending on the selected approach. The purpose of this study was to investigate the risk of femoral head, neck and subtrochanteric fracture following six different core decompression techniques. Materials: Five common and a newly proposed techniques were analyzed in respect to their biomechanical consequences using finite element analysis. The geometry of a femur was reconstructed from computed-tomography images. Thereafter, the drilling configurations were simulated. The strains in the intact and drilled femurs were determined under physiological, patient-specific, muscle and joint contact forces. Findings: The following results were observed: i) - an increase in collapse and fracture risk of the femur head by disease progression ii) - for a single hole approach at the subtrochanteric region, the fracture risk increases with the diameter iii) - the highest fracture risks occur for an 8 mm single hole drilling at the subtrochanteric region and approaches with multiple drilling at various entry points iv) - the proposed novel approach resulted in the most physiological strains (closer to the experienced by the healthy bone). Interpretation: Our results suggest that all common core decompression methods have a significant impact on the biomechanical competence of the proximal femur and impact its mechanical potential. Fracture risk increases with drilling diameter and multiple drilling with smaller diameter. We recommend the anterior approach due to its reduced soft tissue trauma and its biomechanical performance. Highlights: Impact of core decompression techniques on the biomechanical behaviour of the femur Risk of fracture evaluation of different surgical techniques A novel anterior surgical approach results in most physiological strains